Reconfiguring intervention complexity, resilience and the 'local turn' in counterinsurgent warfare - Moe, Louise Wiuff; Muller, Markus M. (Palgrave Macmillan, 2017)
This book is essential reading for anyone interested in understanding recent changes in global liberal governance as well as the growing convergence of military and seemingly non-military domains, discourses and practices in the contemporary making of global political order.